(untitled) (Journal of the College of Basic Education, 2026)
Counseling is one of the most sensitive and important professions in dealing with individuals, due to the information, analysis, and precise treatment it provides for clients’ problems. Therefore, from this perspective, this study focused on identifying Secondary traumatic stress, professional boundary management, and the statistical relationship between them among new counselors. To achieve these goals, the researcher adopted the Secondary Trauma stress Scale (Bride et al., 2004), based on Figley’s (1995) theory and the DSM-IV-TR. It consists of 17 items distributed across three dimensions: Mental Intrusion (1, 4, 5, 10, 12), Avoidance (2, 6, 7, 9, 11, 13, 14), and Irritability or Excessive Arousal (3, 8, 15, 16, 17). It is on a five-point scale (1 = never, 2 = rarely, 3 = sometimes, 4 = often, 5 = always). A professional boundary management scale was also constructed, suitable for the sample. (New counselors) Based on the theory of Herlihy & Corey (1992-2014) and consisting of (20) items with a five-point scale (1 = never, 2 = rarely, 3 = sometimes, 4 = often, 5 = always), the tools were applied to a sample of (150) counselors. After verifying the standard properties, it was found that the research tools have good standard properties. The research results showed that the presence of an average level of secondary traumatic stress among new counselors is attributed to many factors, including the counselor’s experience or not being exposed to sufficient pressures from psychological cases, which will increase the stock of secondary traumatic stress, and its level will rise over time. It also showed the presence of an average level of professional boundary management among new counselors due to the lack of experience and awareness of counseling issues and the lack of intensive professional counseling training. Finally, there is no statistically significant relationship between the two variables, meaning that the level of secondary traumatic stress is not related to the level of professional boundary management among new counselors. This is explained by the fact that professional boundary management here is not the direct factor in reducing or increasing secondary traumatic stress, but rather is influenced by the counselor’s professional experience and personal skills, the degree of organization at work, and the type of training.